Adjuvant Chemotherapy and Radiotherapy in Resected Pancreatic Ductal Adenocarcinoma: A Systematic Review and Clinical Practice Guideline - James J. Biagi; Roxanne Cosby; Mala Bahl; Tarek Elfiki; Rachel Goodwin; Julie Hallet; Khalid Hirmiz; Aamer Mahmud (Current Oncology, 2023)
Pancreatic cancer is the seventh leading cause of cancer deaths worldwide, accounting for 4.7% of all cancer deaths, and is expected to climb significantly over the next decade. The purpose of this systematic review and guidance document was to synthesize the evidence surrounding the role of adjuvant treatment (chemotherapy and chemoradiation therapy [CRT], and stereotactic body radiation therapy [SBRT]) in resected pancreatic ductal adenocarcinoma (PDAC). Systematic literature searches of MEDLINE, EMBASE, and 11 guideline databases were conducted. Both direct and indirect comparisons indicate adjuvant chemotherapy offers a survival advantage over surgery alone. The optimal regimens recommended are mFOLFIRINOX with alternative options of gemcitabine plus capecitabine, gemcitabine alone, or S-1 (which is not available in North America). Trials comparing a CRT strategy to modern chemotherapy regimens are lacking. However, current evidence demonstrates that the addition of CRT to chemotherapy does not result in a survival advantage over chemotherapy alone and is therefore not recommended. Trials evaluating SBRT in PDAC are also lacking. SBRT should only be used within a clinical trial or multi-institutional registry.